Study of serum adenosine deaminase levels in head and neck malignancies - M. S., Sudhakar Rao; R., Reshma P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Head and neck malignancies are the malignancies occurring at various sites like scalp, ear, nose and paranasal sinuses, nasopharynx, oral cavity, oropharynx, hypopharynx, larynx, and salivary glands. There are various biomarkers which aid in early diagnosis and management of head and neck malignancies. In order to study various parameters aiding in early diagnosis, this study has been taken up to estimate serum adenosine deaminase levels among these patients. Methods: Eighty-eight clinically diagnosed head and neck malignancy patients of both genders were included in this study on simple random basis. After obtaining the written informed consent from the patient, a peripheral venous sample of blood was taken and serum ADA levels were estimated. Data was analyzed using IBM SPSS Version 22. Results: Serum ADA levels are found to be statistically significant with respect to various stages of head and neck malignancies including malignancy of unknown origin. Mean ADA level in this study was 30.33 IU/l. Mean ADA levels in MUO, primary tumor with neck secondaries were 37 IU/l, 38.7 IU/l respectively. Mean ADA levels in patients with primary tumor without neck secondaries was 27.9 IU/l. Conclusions: The Serum ADA levels among head and neck malignancy patients including MUO is a simple, inexpensive diagnostic biomarker enzyme which is easy and rapid to estimate. This study emphasizes on using Serum ADA levels as a prognostic indicator among head and neck malignancies who are on various modalities of treatment.